P13 The anatomical and functional characteristics of myocardial scar in MINOCA patients. (7th September 2020) - Lun, Andie; Williams, Matthew; Hussain, Arshan; Bucciarelli-Ducci, Chiara
Abstract : Introduction: Previous research has identified the pattern of scarring associated with different aetiologies of myocardial infarction with non-obstructive coronary arteries (MINOCA). However, the association between the characteristics of scar and the impact these characteristics have on the strain of the myocardium has not been investigated. The purpose of this study is to investigate whether the left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) of the myocardium is affected by the amount and pattern of late gadolinium enhancement (LGE). Methods: 150 patients (mean age 59.0 ± 15.1 years) who were referred for cardiac MRI (CMR) were recruited retrospectively. Patients with known heart failure, previous myocarditis or not meeting the ESC working group definition of MINOCA were excluded. All patients were scanned at least 28 days after presentation. Their CMRIs were analysed for LVEF, GLS and amount of LGE. SPSS was used to run linear regression, T- test and Kolmogorov-Smirnov Test (K-S) for data analysis. Results: 57 of the 150 patients had LGE (mean LGE size 1.43g ± 2.89). There was no significant correlation between the amount of scarring and GLS (p=0.350) overall. However there was a significant association between the amount of ischaemic scar and worsening GLS (p=0.025). There was no significant difference in GLS between ischaemic and non- ischaemic patterns of LGE (t=0.914, p=0.188). Conclusion: The amount and pattern of scar do not independently have a direct impact on the GLS of the myocardium in MINOCA patients. Our data suggests that there is a significant correlation between the amount of ischaemic scar and the GLS.